2019
DOI: 10.1002/cam4.2742
|View full text |Cite
|
Sign up to set email alerts
|

EBV status has prognostic implication among young patients with angioimmunoblastic T‐cell lymphoma

Abstract: Epstein-Barr virus (EBV)-positive B cells have been detected in 66%-86% of patients with angioimmunoblastic T-cell lymphoma (AITL). However, it remains controversial whether EBV status has an impact on the survival of patients with AITL. In this study, we aimed to reevaluate the impact of EBV on the clinicopathological characteristics of AITL. In particular, we focused on the impact of EBV in younger patients with AITL. In total, 270 cases of AITL were studied. Epstein-Barr virus-positive B cells were detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
(58 reference statements)
1
17
2
Order By: Relevance
“…Kaplan-Meier Survival analysis was performed with regards to EBV infection, and the results demonstrated no improved overall survival for EBV positive cases. Our results do not confirm these previous findings of Eladl et al ( 50 ) but our sample size is small. Another study by Hoffman et al ( 51 ) assessed the association between EBV infection and diffuse large B-cell lymphoma (DLBCL) occurring in PTCL, and reported that patients with PTCL and DLBCL frequently have EBV infected B-cells, suggesting an important role of EBV in B-cell transformation.…”
Section: Discussioncontrasting
confidence: 99%
“…Kaplan-Meier Survival analysis was performed with regards to EBV infection, and the results demonstrated no improved overall survival for EBV positive cases. Our results do not confirm these previous findings of Eladl et al ( 50 ) but our sample size is small. Another study by Hoffman et al ( 51 ) assessed the association between EBV infection and diffuse large B-cell lymphoma (DLBCL) occurring in PTCL, and reported that patients with PTCL and DLBCL frequently have EBV infected B-cells, suggesting an important role of EBV in B-cell transformation.…”
Section: Discussioncontrasting
confidence: 99%
“…T cell lymphoma is a rare form of cancerous lymphoma affecting T cells, which represents less than 15% of all non-Hodgkin's diseases. Various risk factors and virus infections such as Epstein Barr virus and human T cell leukemia virus-1 account for the progression of T cell lymphoma [ 25 , 26 ]. Unfortunately, there is no effective therapeutics for the debilitating disease so far.…”
Section: Discussionmentioning
confidence: 99%
“…e ultimate differentiation of EBV-infected B cells into PC was related to EBV replication, which is suppressed by a strong T cell immune response in EBV-seropositive healthy people [32]. EBVpositive B cells can be detected in 66-86% patients of AITL, on account of immunosuppression due to AITL [33]. Tumor T cells, cytokines, and EBV infection may potentially cause polyclonal plasma cell expansion.…”
Section: Discussionmentioning
confidence: 99%